Die Wêreldbond van Gereformeerde Kerke, die Nederduitse Gereformeerde Kerk en "n status confessionis teen die teologiese en morele regverdiging van apartheid - Strauss, Piet J. (HTS teologiese studies, 2015)
The World Alliance of Reformed Churches, the Dutch Reformed Church and a status confessionis against the theological and moral justification of apartheid. In 1982 the World Alliance of Reformed Churches (WARC) announced a status confessionis against the theological and moral justification of apartheid. It expelled two member churches, the Dutch Reformed Church (DRC) and the Netherdutch Reformed Church of Africa (Nederduitsch Hervormde Kerk van Afrika) because of their known support of apartheid. This situation could only be changed if these two churches were to unequivocally reject apartheid on the basis of a status confessionis and show specified practical examples of this rejection. The meaning of a status confessionis as applied by the WARC is analysed. The reason why the WARC came to a status confessionis is historically investigated. The reaction of the DRC to this resolution and its readmittance as a member of the WARC is clarified. Attention is also given to the condition that accepting a status confessionis against the support of apartheid does not mean – for the WARC at least – that a new confession of faith should follow from this.